The Effect Of Mean Length Utterance On The Complexity Of Syntactic Structure In 4-6 Year Old Children - Rahmaningtyas, Ainulia Safira; Pratomo, Hafidz Triantoro Aji (Poltekkes Kemenkes Surakarta, 2023)
Background: Mean Length Utterance (MLU) results from dividing the total morphemes by the child’s number of utterances. MLU is an indicator of gross language development in children. The more the vocabulary the higher will be the development of language acquisition and so will be the MLU score and the more complex will be the sentence structure so that language development can be known, especially grammatical aspects including syntax and morphology. Syntactic complexity is the range of sentence complexity levels based on its syntactic structural components. This study aims to determine whether or not there is an effect of Mean Length Utterance (MLU) on the complexity of the syntactic structure of children 4-6 years old in Demakan Village. Methods: This study used a quantitative method, correlational design and cross sectional approach. The populations in this study were children aged 4-6 years in TK Desa Demakan 01 and Klinik Belajar Bahasa Bicara Sukoharjo. Sampling was conducted using purposive sampling with 30 children. 15 children aged 4 years, 9 children 5 years old, and 6 children 6 years old. This study conducted in November 2022 until Februari 2023. The spontaneous language sampling analysis used to measure MLU and syntactic complexity. Results: The results of the statistical correlation test using Spearman-Rank analysis obtained a p value of 0.001 (p <0.05) meaning that Ha is supported or there is an effect of MLU on the complexity of the syntactic structure of children 4-6 years in Demakan Village. The r value of 0.644 implies that there is a